Climate Change and Maritime Claims in the Arctic - Daniel Schneider 1993- (2024)
This paper revolves around the question of how the geopolitical situation in the Arctic is influenced by climate change, and how local conflicts should be viewed against the backdrop of the international law of the sea. Initially, the geopolitical situation in the Arctic region is discussed, based mainly on the Arctic strategies published by the Arctic states themselves. That analysis is then to be supplemented by a review of relevant secondary literature. Thereafter, the legal status of the Arctic is addressed, whereby those legal norms and treaties concerning the status of the Arctic, creating the legal framework there, are analysed. The pertinent conflicts identified in the first chapter are accordingly subjected to a legal assessment, based on the author's own legal opinion alongside additional pertinent secondary legal literature. From that, it will become evident how incomplete the legal framework in the region currently presents itself, and how international maritime law, in some cases, promotes conflicts to arise in the region, rather than helping to prevent them. Following that, the consequences of climate change for the region are outlined. Particular attention is paid to how climate change relates to the conflicts taking place in the Arctic, with an additional focus on the extent to which climate change creates, or influences, regional conflicts. From that, the conclusion will emerge that climate change may create new conflicts as well as fuelling old ones. Subsequently, the legal effects of climate change are also elaborated on, i.e. the impact of a changing geography on maritime zones. It will become clear that some of these maritime zones are shifting in line with changing coastlines, and that this fact must therefore be considered in potential future treaties. In addition, it will be assessed that these developments present a risk of contracting parties invoking Art. 62 VCLT, due to changing circumstances caused by climate change, and thus may elect to withdraw from the treaty. The current Arctic ...